Expert System Disease Diagnosis and Drug Relation Amor Pharmacy - Ilyas Ilyas (Journal of Intelligent Decision Support System (IDSS), 2020)
The development of information and communication technology today has a major influence on various aspects of life, even human behavior and activities now depend a lot on information and communication technology. One example is the use of expert system-based technology. The development of expert system-based applications has been in great demand since 1950, with a fairly wide coverage area. Expert systems in organizations are aimed at adding value, increasing productivity and managerial areas that can draw conclusions quickly. In this study an application was developed "Expert System for Disease Diagnosis and Drug Relation". This application was built to be an alternative in diagnosing a type of disease based on the symptoms felt by the user, so that the user finds a solution to the problem at hand. From the results of tests carried out using the black box method, it can be concluded that this application can function well. And can provide convenience for users in diagnosing diseases and recommending what drugs are suitable for people with the disease.